Analisis CAR, NPL, BOPO dan LDR terhadap Profitabilitas - Abdul Aziz Suryadi; Risal Rinofah; Pristin Prima Sari (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
This research aimed to examine the effect of Capital Adequacy Ratio (CAR), Non Performing Loan (NPL),Operating Expenses Operating Income (BOPO) and Loan to Deposite Ratio (LDR) ratios on profitability (ROA). This type of research is quantitative research. The sample selection method in this research used purposive sampling method. The sample used was 20 of 45 banking companies listed on the Indonesia Stock Exchange with the periode 2016-2020. The analytical method used was multiple linear regression analysis using the SPSS version 22 program. The result showed that the Capital Adequacy Ratio (CAR) t test had a significant effect on profitability (ROA) partially, Operating Expenses Operating Income (BOPO) has a negative effect on profitability(ROA) partially, then Non Performing Loan (NPL) and Loan to Deposite Ratio (LDR) have a positive and not significant effect on profitability (ROA). And from the result of the f test, the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), Operating Expenses Operating Income (BOPO) and Loan to Deposite Ratio (LDR) variables have a simultaneous effect on profitability (ROA). Keywords: CAR, NPL, BOPO, LDR, ROA